A descriptive survey of the values of selected interior design students in relation to their attitudes towards social design - Dela Cruz, Maria Freza Sarah F.; Florendo, Raquel B. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
Anderson (2007) argues that interior design needs to focus on contributing to the society to gain public recognition. Service learning is incorporated in the curriculum of interior design to emphasize the need to provide service to the public, however, it is necessary to first assess if there is the need to enrich the values of interior design students and a system that will promote the use of social design in the professional practice. This study determined the relation of 46 students level of values of giving in relation to their attitude towards social design. As a descriptive survey, both quantitative and qualitative methods were used in data gathering and analysis. A purposive sampling method was used to select respondents from the third year and fourth year students of the BS Interior Design program during the second semester of AY 2016-2017. Using convenience sampling method, focus group discussion participants were selected from survey respondents who were willing and available to elaborate their answers. A 60-item survey questionnaire and a semi-structured focus group discussion guide was used to derive numerical scores corresponding to the students level of values and attitude towards social design. Correlated results showed that the respondents generally have a moderate level of positive values and moderate level of positive attitudes towards social design. The level of values among the students and their attitude towards social design were found to have a direct relationship. The wide range of students scores implies that positive values of giving and positive attitude towards social design are not widespread among all students. It is suggested that higher education includes value education to enhance the level of positive values among students. An inclusion of the concept of social design could also be emphasized in the curriculum to let the students have an in-depth understanding of the concept, better comprehension of its importance, increase the level of support and confidence, and teach students not only to overcome barriers but provide alternatives and feasible solutions.
submitted June 2017
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Unversity of the Philippines (Diliman) College of Home Economics -- Students; Interior designers -- Values